3 - The food security concept: Definition, conceptual frameworks, measurement, and operationalization - Makombe, Godswill (Africa Development, 2024)
The concept of food security appeared in policy forums and documents during the 1970s as a concern largely for developing countries. Today, food security stands centre stage in developing and developed nations. It is a multidimensional concept, which rests on the four pillars of availability, access, utilisation and stability. As our understanding of this complex concept deepens, there are persuasive arguments to add the elements of food agency, food sovereignty and food sustainability, to make it a six-pillar framework. The argument is that this framework better informs policy and global responses to short- and long-term food security challenges. One of the main challenges of the concept of food security is its measurement. This arises due to the fact that there are multiple units of analysis at macro, meso and micro levels. Even the pillars of food security are measured at different scales. This has resulted in the proliferation of hundreds of food security metrics and definitions. The currently accepted definition of food security encapsulates the complexity of the concept but does not assist in developing appropriate metrics. Development projects in Africa that state food security as an objective need to develop relevant food security definitions to guide the assessment of achieving that objective, otherwise measuring its success is reduced to an evaluation of increase in food production—yet we know food security goes beyond production.